IMPORTANCE OF STRESS-TESTING IN RISK ASSESSMENT OF COMMERCIAL BANKS (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article provides information on importance of using stress-testing in assessing risks in the activity of commercial banks.